A reversible chemical cell of molten potassium nitrate - Arvia, Alejandro Jorge (1967)
A reversible galvanic cell of molten potassium nitrate is described. It is represented by the following scheme: K(1)/KNO3(l)/NO2(g),O2(g)/Pt(s). The theoretical standard emf calculated from thermochemical data for the reaction K(I) + NO2(g) + ½O2(g) = KNO3(l) is in very good agreement with the one deduced from the experimental results. The standard emf of the cell is given by E ° = 5∙440 + 3∙812 × 10-4T 1n T - 6∙231 × 10-8T2 + 2∙623/T - 5∙156 × 10-3T.